Heart’s Unreason: A Reading of Edelman’s Anti-Futurism through Bataille - Panayotov, Stanimir (Identities: Journal for Politics, Gender and Culture, 2011)
Author(s): Stanimir Panayotov Title (English): Heart’s Unreason: A Reading of Edelman’s Anti-Futurism through Bataille Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 8, No. 1 (Winter 2011) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 129-138 Page Count: 10 Citation (English): Stanimir Panayotov, “Heart’s Unreason: A Reading of Edelman’s Anti-Futurism through Bataille,” Identities: Journal for Politics, Gender and Culture, Vol. 8, No. 1 (Winter 2011): 129-138.